Compound polysaccharides ameliorate experimental colitis by modulating gut microbiota composition and function. Issue 9 (31st January 2019) - Cai, Ying; Liu, Wen; Lin, Yixuan; Zhang, Shaobao; Zou, Baorong; Xiao, Dan; Lin, Lei; Zhong, Yuping; Zheng, Haihui; Liao, Qiongfeng; Xie, Zhiyong
Abstract: Background and Aim: Inflammatory bowel disease results from a dysregulated immune response to intestinal microbial flora in individuals with genetic predisposition(s). This study aimed to determine the effects of compound polysaccharides (CP) containing yam polysaccharide and inulin on the rat model of colitis induced by 2, 4, 6‐trinitrobenzenesulfonic acid (TNBS) and to explain the mechanism in terms of gut microbiota composition and function. Methods: Male SD rats were divided into three groups: the control group, the model group, and the CP group. Disease activity index, serum myeloperoxidase level, and the composition and function of gut microbiota were analyzed. Results: The data in the study showed CP reduced inflammation in the rat model of colitis induced by TNBS and ameliorated the experimental colitis. The results also indicated that CP not only reversed TNBS‐induced gut dysbiosis‐indexed by increased short‐chain fatty acids (SCFAs)‐producing bacteria, lactic acid‐producing bacteria, and decreased Bacteroides, Proteobacteria as well as sulfate‐reducing bacteria, but also restored the dysregulated microbiota function of colitic rats into a normal condition, including an improvement on basic metabolism and a reduction on oxidative stress, cell motility, signal transduction, xenobiotics biodegradation, and metabolism as well as pathogenesis processes. Conclusions: Compound polysaccharides ameliorated the experimental colitis of rats induced by TNBS by modulating the gut microbiota composition and function profiles, which makes it possible to be used as prebiotic agents to treat gut dysbiosis in colitis individuals.